Necrotizing fasciitis resembled acute coronary syndrome: A case report - Matin Sepehrinia; Faeze Yousefi; Adib Valibeygi; Abdulhakim Alkamel (Clinical Case Reports)
Key Clinical Message Chest pain is a frequent complaint in emergency departments, with various differential diagnoses from benign to life‐threatening. Hereby, we described a 60‐year‐old man presented with chest pain and hypotension who initially misdiagnosed as acute coronary syndrome, but was ultimately diagnosed with necrotizing fasciitis. This case highlights the importance of considering rare causes of chest pain.